Comparative outcomes of ureteroscopy and percutaneous nephrolithotomy in CKD patients with renal calculi: a propensity-matched cohort study - Chiou, Jiun-Kai; Wu, Jheng-Yan; Lin, Yu-Min (Frontiers in Medicine, 2025)
BackgroundKidney stones frequently coexist with chronic kidney disease (CKD), sharing common risk factors and leading to adverse outcomes. While percutaneous nephrolithotomy (PCNL) and ureteroscopy (URS) are both effective treatment options, the safety of PCNL has been well-established in CKD patients, whereas the safety profile of URS remains less clear.MethodsA retrospective cohort study using the TriNetX database was conducted to compare outcomes in CKD patients undergoing URS or PCNL. Patients aged ≥18 years with a diagnosis of renal stones and CKD were included, excluding those on dialysis. Propensity score matching (PSM) was performed to balance baseline characteristics. The primary outcome was the 5-year rate of major adverse kidney events (MAKE), a composite of mortality, dialysis initiation, and worsened renal function. Secondary outcomes included all-cause mortality and dialysis dependence. Subgroup and sensitivity analyses were performed to ensure robustness.ResultsOf 5,470 eligible patients, 837 underwent URS and 4,633 underwent PCNL, with 723 patients matched in each group post-PSM. There was no significant difference in MAKE between URS and PCNL (HR 0.93; 95% CI 0.68–1.28; p = 0.6952). All-cause mortality (HR 0.98; 95% CI 0.70–1.36; p = 0.9125) and dialysis dependence (HR 0.57; 95% CI 0.23–1.38; p = 0.2128) were also similar. The limitation of this study is the lack of data on stone size and location.ConclusionIn CKD patients with renal stones, URS demonstrated comparable safety and efficacy compared to PCNL, with no significant differences in MAKE, all-cause mortality, or dialysis dependence over 5 years. However, the lack of information regarding stone size, anatomical location, and procedure-specific details (e.g., device use or surgical technique) is a major limitation of our study.